2020
DOI: 10.1103/physrevaccelbeams.23.021002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the emittance growth due to decoherence in collision at the Large Hadron Collider

Abstract: The transverse emittance growth rate of colliding hadron beams driven by external sources of noise is investigated based on existing analytical model as well as on macro-particle simulations and comparison to experimental data at the Large Hadron Collider (LHC). It is shown that an analytical description of the emittance growth rate neglecting the existence coherent beam-beam mode can nevertheless provide accurate estimate for operational conditions, featuring notably a high chromaticity. The model is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Though the TFB performance during the LHC Runs I (2009-2013) and II (2013-2018) was greatly sufficient for the LHC operation, recent studies showed that the TFB noise floor in the LHC must be reduced by at least factor of two in order to operate the machine with large beambeam tune shift as foreseen in the High Luminosity (HL) LHC [6] and suppress the risk of loss of Landau damping by noise [7]. Improvement by factor of 4 is required to recover an emittance growth rate in the order of 2% per hour as in the present LHC.…”
Section: Performance Of the Old Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the TFB performance during the LHC Runs I (2009-2013) and II (2013-2018) was greatly sufficient for the LHC operation, recent studies showed that the TFB noise floor in the LHC must be reduced by at least factor of two in order to operate the machine with large beambeam tune shift as foreseen in the High Luminosity (HL) LHC [6] and suppress the risk of loss of Landau damping by noise [7]. Improvement by factor of 4 is required to recover an emittance growth rate in the order of 2% per hour as in the present LHC.…”
Section: Performance Of the Old Systemmentioning
confidence: 99%
“…With the majority of the signal processing chain of the LHC TFB being digital, the beam position measurement subsystem is considered to define the noise performance of the whole LHC TFB system, therefore the effort to lower it focuses on improving the beam position measurement subsystem. The noise floor of the TFB system can be determined only indirectly: either beam based by measurement of transverse emittance blow-up [6], or by analysis of the beam position measurement hardware [9].…”
Section: Performance Of the Old Systemmentioning
confidence: 99%
“…A transverse active damper (ADT) is present in the LHC [75] and, although its effect on the beam dynamics is not implemented in SixTrack yet, analytical models can be used to estimate the emittance growth suppression factor [76], which depends only on the tune spread and ADT gain. Thus, considering the nominal ADT damping time of 50 turns [17] and a tune spread of about 10 −4 with non-colliding beams, a suppression of the emittance growth by a factor about 10 3 is expected, leading to the estimates shown in Fig.…”
Section: Emittance Growth Mitigationmentioning
confidence: 99%